HIDROLISIS BEBERAPA JENIS XILAN DENGAN ENZIM XILANOLITIK TERMOFILIK REKOMBINAN - Ni Nyoman Tri Puspaningsih; Hery Suwito; Sri Sumarsih; Ali Rohman; One Asmarani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
The aims of this research were to know the ability of recombinant xylanolytic enzyme from recombinant E. coli DH5a (pTP510) to hydrolyze several commercial xylan and analysis the reduction sugar product. Recombinant xylanolytic enzyme (exo-xylanase, b-xylosidase and a-L-arabinofuranosidase) could hydrolyzed several commercial xylan (oat-spelt xylan, birchwood, wheat, rye, and arabinan) with xylanolytic activities are: oat-spelt xylan (1.73 U/mL), birchwood (0.92 U/mL), wheat (6.52 U/mL), rye (4.94 U/mL), and arabinan (3.40 U/mL). Xylanolytic enzyme assay use specific substrate p-nitrophenyl-b-D-xylopyranoside (pNP-X) shown xylosidase activity 15.869 U/mL. Hydrolysis product was analyzed by HPLC. The results showed that xylose, arabinose, and xylo-oligosaccharide were produced from birchwood, wheat, rye, and arabinan hydrolysis, although xylose and arabinose were produced from hydrolysis of oat-spelt xylan.